2022
DOI: 10.21037/tgh-20-84
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of endoscopic ultrasound-guided radiofrequency ablation for management of pancreatic lesions: a systematic review and meta-analysis

Abstract: Background: Radiofrequency ablation (RFA) has been used to treat various abdominal tumors including pancreatic tumors. Multiple approaches such as laparoscopic, open, and percutaneous have been used for pancreatic tissue ablation. More recently, endoscopic ultrasound (EUS)-guided RFA has emerged as a new technique for pancreatic tissue ablation. The role of EUS-RFA in management of pancreatic lesions is still not well-established. In this study, our aim is to assess efficacy and safety of EUS-RFA for managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…This modality induces coagulative necrosis via directed thermal energy, and it has been used in the treatment of other solid tumors. Several studies have demonstrated this technique is safe and with minimal post-procedure complications [ 64 , 65 ]. From a technical standpoint, clinical success appears to be higher for insulinomas that are located in head or neck of the pancreas [ 65 ].…”
Section: Surgical Management Of Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modality induces coagulative necrosis via directed thermal energy, and it has been used in the treatment of other solid tumors. Several studies have demonstrated this technique is safe and with minimal post-procedure complications [ 64 , 65 ]. From a technical standpoint, clinical success appears to be higher for insulinomas that are located in head or neck of the pancreas [ 65 ].…”
Section: Surgical Management Of Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%
“…From a technical standpoint, clinical success appears to be higher for insulinomas that are located in head or neck of the pancreas [ 65 ]. While studies are limited, endoscopic ultrasound-guided radiofrequency has demonstrated symptomatic improvement after radiofrequency [ 64 ]. Additional studies are needed, but minimally invasive techniques for the treatment of insulinomas are feasible and may provide benefit by way of sparing healthy pancreatic tissue.…”
Section: Surgical Management Of Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%
“…Overall, EUS-RFA appears to be fairly safe with a recent meta-analysis of 115 patients (with various pancreatic lesions being treated) demonstrating a pooled adverse event rate of 6.7% (95% CI: 3.4–11.7, I2 = 34.0%), the commonest being acute pancreatitis (3.3%) ( 139 ).…”
Section: Eus-guided Interventions In Pancreatic Cancermentioning
confidence: 99%
“…Skuteczność oceniono na 88,9%, zaś odsetek zdarzeń niepożądanych 6,7%. [15] W przypadkach guzów złośliwych można rozważyć usunięcie zmiany razem z regionalnym układem chłonnym. Przerzuty do wątroby mogą być również usunięte lub leczone za pomocą embolizacji błony śluzowej, radioembolizacji (SIRT), ablacji prądem o częstotliwości radiowej (RFA), ablacji mikrofalowej i krioablacji, zogniskowanych ultradźwięków o dużej intensywności (HIFU), lasera, brachyterapii i nieodwracalnej elektroporacji (IRE) w zależności od lokalnej dostępności.…”
Section: Leczenieunclassified